Influence of Life Style and Financial Literacy to Consumptive Behavior through Self-Control of Unisnu FEB College Students Jepara - Halimatussakdiyah, Halimatussakdiyah; Martono, S.; Sudarma, Ketut (Universitas Negeri Semarang, 2019)
Consumptive behavior as buying intention keeps increasing to get satisfaction in term of good and service ownership without considering its uses. This behavior may be instilled into life style of teenagers. They will grow to be consumptive mature individuals if they are not guided. This research aims to analyze and find empirical evidence of life styles, financial literacy through self-control as intervening variable to consumptive behaviors of the students. This qualitative correlational research used proportional stratified random sampling. There were 121 students selected. Technique of analyzing data was lane analysis. The findings showed life style, financial literacy, and self-control influenced consumptive behavior. Furthermore, life style and financial literacy influenced consumptive behavior through self-control as mediator.